5 - Covid-19 Border Policing in Ghana and its Impact on Trans-border Migration and Healthcare in West Africa - Adu-Gyamfi, Samuel; Paalo, Sebastian; Issifu, Abdul Karim (Africa Development, 2024)
The discourses and practices surrounding migration and health have taken a dramatic turn since the outbreak of the Covid-19 pandemic. Experts are more concerned about the consequences of the pandemic on these factors in Africa, given the continent’s weak economies and poor health sector, which portends a difficult post-pandemic recovery. However, the discussions have not engaged with two key effects of the coronavirus: the health implications not only on the general populace but also along border towns, and the dilemma of a ‘new’ (il)legal migration. Drawing on Ghana’s border policing as a Covid-19 pandemic governance strategy, coupled with existing debates on health, politics, migration and development, we argue that border policing is likely to create two emerging threats. First, it could cause a ‘new’ health dilemma – hindering long-standing cross-border healthcare access by ECOWAS citizens. Second, sustained border restrictions could deepen the intricacies of migration in West Africa, including the promotion of ‘elite migrants’ over migrants who are seeking a basic livelihood, the changing fate of undocumented migrants, new security threats at border town , and a possible redefinition of traditional rural–urban migration in Africa.